The Ethics of Terminal Care - Loewy, Erich E.H. author. aut Link
XV, 181 p.
Keywords: Today we have more control over how we live and how we die than we ever had before. This fact has produced many ethical problems. While much about life is biologically determined, much else is determined by the social circumstances surrounding it. Unfortunately, little energy is spent dealing with the social and psychological factors within which the medical/biological factors are imbedded. In this volume the authors examine some of the medical social and psychological conditions which affect the way we die. Important topics covered include attitudes toward death; suicide, assisted suicide and euthanasia; hospice and pain management. This volume will be of interest to all who work with terminally ill patients.